Clinical Factors Associated with Brain Volume Reduction in Systemic Lupus Erythematosus Patients without Major Neuropsychiatric Manifestations - Liu, Shuang; Cheng, Yuqi; Zhao, Yueyin; Yu, Hongjun; Lai, Aiyun; Lv, Zhaoping; Xu, Xiufeng; Luo, Chunrong; Shan, Baoci; Xu, Lin; Xu, Jian (Frontiers in Psychiatry, 2018)
The study was aimed to find structural brain changes in systemic lupus erythematosus patients without major neuropsychiatric manifestations (non-NPSLE) using quantitative magnetic resonance imaging (MRI), and possible associations with clinical characteristics. 89 non-NPSLE patients with normal conventional MRI and 84 healthy controls were recruited. The whole brain grey matter volume (GMV) and white matter volume (WMV) were calculated for each individual. We found obvious GMV and WMV reduction in SLE group compared with healthy controls. Female patients showed significant reduction of GMV and WMV compared with male patients. Patients treated with immunosuppressive agents (ISA) showed less WMV reduction than those without. Cognitive impairment was the most common subclinical neuropsychiatric manifestation and had a prevalence of 46.1%. Association between WMV reduction with cognitive impairment was found. Thus we concluded that structural brain atrophy could happen even before occurrence of obvious neuropsychiatric signs and symptoms, and was associated with subclinical symptoms such as cognitive impairment. ISA treatment might have a protective effect on the brain atrophy. Early treatment might prevent the progressive damage to the brain. More studies are needed to fully understand the complicated underlying mechanisms of brain atrophy in SLE.